Identifying and determining the weight of personality indicators effective in establishing educational and training interaction between Iranian paramedical instructors and students in clinical training situations using the Analytic Hierarchy process (AHP) method - Nouri Kalkhoran, Firouz; Arman, Pegah; salehi, Iraj; Khalafi, Ali; Safari, Mohammad Reza (International journal of Africa nursing sciences, 2025)
Clinical education is one of the most important goals in medical science education. Various factors affect the quality of clinical education for students. One of the most significant factors is the personality traits of students, which can aid them in the learning process and lead to more effective education. This research was organized using a mixed-methods approach. In the qualitative section, aimed at identifying and determining the dimensions of applied personality traits for creating more effective interactions, two methods—exploratory and document analysis—were used. First, with a purposive sampling method, 20 experts were selected for interviews, which were organized using a semi-structured method and categorized using Cohen’s kappa test. In the second part, a questionnaire was organized based on the census method to determine the weight of each personality dimension and sent to 15 instructors. The quantitative data were analyzed using the Analytical Hierarchy Process (AHP) method and Expert Choice software. Data: The results showed that the weight of personality dimensions in establishing teaching and educational interactions between instructors and paramedical students in clinical educational settings indicates that traits such as empathy, interpersonal sensitivity, ambition, anxiety, etc., can be beneficial in the students’ learning process. By identifying the effective traits of students in clinical education, it is possible to better recognize the strengths and weaknesses of each student and design more precise educational programs to enhance student learning.